PENGGUNAAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA AJAR YOUTUBE DAN LIVEWORKSHEETS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMK NEGERI 1 HANAU - Sofiati Sofiati; Walter Punding; Riki Walinono (PINISI :Journal of Teacher Professional, 2022)
This research aim to for the mendeskripsikan of study use model of Problem Based Learning ( PBL) with media of Youtube and of liveworksheets able to improve result learn at items operate for matrix.Research method the used is research of class action which consist of four phase, that is planning, execution, and observation of refleksi. Research Subjek is entire/all class student of XI TKJ amounting to 29 student, while research object is the overall of result and process pernbelajaran of mathematics use model of Problem Based Learning ( PBL) with media of Youtube and of liveworksheets able to improve result learn at items operate for matrix.Research executed in three cycle. Result of research show activity learn student mount seen from more and more student which join in in activity of group discussion and group presentation. And result learn student even also experience of increase each;every its cycle, that is cycle of I is 54,24, cycle of II is 72,76 and cycle to III is 81,69. And at third cycle of value all student also have reached indicator of reached.